2019
DOI: 10.1063/1.5075531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the introduction of a chromium oxide monolayer at the C60/Fe(001) interface

Abstract: The introduction of a two-dimensional oxide layer at the interface between an organic semiconductor and a ferromagnetic metal (spinterface) can help in tailoring the formation of spin-polarized hybridized interface states. Here, we consider the case of a Cr 4 O 5 monolayer at the C 60 =Fe(001) interface, which is already known to feature the occurrence of spin-polarized states in the fullerene molecules. In this work, we employ scanning tunneling microscopy/spectroscopy and photoemission spectroscopy to show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Ab initio calculation have been performed in the framework of Density Functional Theory (DFT), following the scheme of our previous works [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ab initio calculation have been performed in the framework of Density Functional Theory (DFT), following the scheme of our previous works [14][15][16].…”
Section: Methodsmentioning
confidence: 99%
“…In recent works [14][15][16] some of us focused on the C 60 /Fe(001) interface, both on the experimental and theoretical viewpoint. We demonstrated that the induced magnetic properties on the molecules depend on the spin polarization of the substrate states interacting with the molecule itself and by their decay toward vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…The Molecular Spintronics special topic in the Journal of Applied Physics offers an overview of the most active research areas currently under investigation in the broad field of molecular spintronics. In particular, featured topics include spin readout and manipulation in single-molecule magnets, [16][17][18] hybrid spin states and magnetic coupling at molecule/metal interfaces, [19][20][21][22] spin transport across ultrathin molecular monolayers 23 and molecular films with novel experimental techniques, 24 and novel promising materials for molecular spintronics such as organic radicals. 25,26 A particular emphasis is devoted to single-molecule spintronics for quantum computing, [16][17][18] with two works demonstrating the potential of one among the prototypical single-molecule magnets (TbPc 2 ) as quantum bits.…”
Section: Summary Of Areas Coveredmentioning
confidence: 99%
“…19 In their study, they show that the magnetization of an atomically thin Ni film, which points out-of-plane in the case of the pristine film, is switched to in-plane when it is covered by a few monolayers of a paramagnetic molecule. The interface between molecules and an ultrathin molecular layer is the topic of the work by Brambilla and co-workers, 21 who focus on the interface between chromium oxide monolayers and C 60 . In this case, a hybrid state appears with peculiar spin polarization.…”
Section: Summary Of Areas Coveredmentioning
confidence: 99%
See 1 more Smart Citation